Antibody isotype diversity against SARS-CoV-2 is associated with differential serum neutralization capacities - Maria G. Noval (Nature Portfolio, 2021)
Abstract Understanding antibody responses to SARS-CoV-2 is indispensable for the development of containment measures to overcome the current COVID-19 pandemic. Recent studies showed that serum from convalescent patients can display variable neutralization capacities. Still, it remains unclear whether there are specific signatures that can be used to predict neutralization. Here, we performed a detailed analysis of sera from a cohort of 101 recovered healthcare workers and we addressed their SARS-CoV-2 antibody response by ELISA against SARS-CoV-2 Spike receptor binding domain and nucleoprotein. Both ELISA methods detected sustained levels of serum IgG against both antigens. Yet, the majority of individuals from our cohort generated antibodies with low neutralization capacity and only 6% showed high neutralizing titers against both authentic SARS-CoV-2 virus and the Spike pseudotyped virus. Interestingly, higher neutralizing sera correlate with detection of -IgG, IgM and IgA antibodies against both antigens, while individuals with positive IgG alone showed poor neutralization response. These results suggest that having a broader repertoire of antibodies may contribute to more potent SARS-CoV-2 neutralization. Altogether, our work provides a cross sectional snapshot of the SARS-CoV-2 neutralizing antibody response in recovered healthcare workers and provides preliminary evidence that possessing multiple antibody isotypes can play an important role in predicting SARS-CoV-2 neutralization.